Multiple fast homoclinic solutions for a class of second-order differential systems with $p$-Laplacian - Selmi, Wafa (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.9We study the existence of multiple fast homoclinic solutions for a class of second-order differential systems with $p$-Laplacian by using the minimax methods in the critical-point theory.